A comparison of the anticancer properties of isoxanthohumol and 8‐prenylnaringenin using in vitro models of colon cancer. (30th January 2013) - Allsopp, Philip; Possemiers, Sam; Campbell, David; Gill, Chris; Rowland, Ian
Abstract : The hops plant ( Humulus lupulus L .) is an essential ingredient in beer and contains a number of potentially bioactive prenylflavonoids, the predominant being the weakly estrogenic isoxanthohumol (Ix), which can be converted to the more strongly estrogenic 8‐PN by the colonic microbiota. The aim of this study was to investigate the biological activity of 8‐PN and Ix using in vitro models representing key stages of colorectal carcinogenesis, namely cell growth and viability (MTT assay), cell‐cycle progression (DNA content assay), DNA damage (Comet assay), and invasion (Matrigel assay). A significant decrease in Caco‐2 cell viability was noted after both 8‐PN and Ix treatments at the higher doses (40 and 50 μM, respectively) although the impact on cell cycle differed between the two compounds. The decreased cell viability observed after Ix treatment was associated with a concentration‐dependent increase in G2/M and an increased sub‐G1 cell‐cycle fraction, whereas treatment with 8‐PN was associated with an elevated G0/G1 and an increased sub‐G1 cell‐cycle fraction. Significant antigenotoxic activity was noted at all 8‐PN concentrations tested (5–40 μM). Although significant antigenotoxic activity was also noted with Ix treatment at ≤25 μM, at a higher dose, Ix itself exerted genotoxic activity. In a dose‐dependent manner, both compounds inhibited HT115 cell invasion with reductions up to 52 and 46% for Ix and 8‐PN, respectively, in comparison to untreated cells. This study demonstrated that both Ix and its gut microbial metabolite 8‐PN exert anticancer effects on models of key stages of colon tumourigenesis. © 2013 BioFactors, 39(4):441–447, 2013